2022
DOI: 10.1111/jam.15574
|View full text |Cite
|
Sign up to set email alerts
|

Plant-associated endophytic fungi as potential bio-factories for extracellular enzymes: Progress, Challenges and Strain improvement with precision approaches

Abstract: There is an intricate network of relations between endophytic fungi and their hosts that affects the production of various bioactive compounds. Plant-associated endophytic fungi contain industrially important enzymes and have the potential to fulfil their rapid demand in the international market to boost business in technology.Being safe and metabolically active, they have replaced the usage of toxic and harmful chemicals and hold a credible application in biotransformation, bioremediation and industrial proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 211 publications
0
10
0
Order By: Relevance
“…The fungi that produced the most enzymes were Aspergillus japonicus (6 enzymes) and Clabosporium cladosporioides (5 enzymes). These hypersecretory endophytes can provide us with a wide range of enzymes that are physiologically important for host metabolism, as well as being useful to industries around the world [25,60] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fungi that produced the most enzymes were Aspergillus japonicus (6 enzymes) and Clabosporium cladosporioides (5 enzymes). These hypersecretory endophytes can provide us with a wide range of enzymes that are physiologically important for host metabolism, as well as being useful to industries around the world [25,60] …”
Section: Discussionmentioning
confidence: 99%
“…These hypersecretory endophytes can provide us with a wide range of enzymes that are physiologically important for host metabolism, as well as being useful to industries around the world. [25,60] Among the enzymes studied, L-asparaginase was an important chemical substance with proven therapeutic efficacy [35] against acute lymphoblastic leukemia (ALL). Studies have demonstrated the efficacy of this substance isolated from Gram-negative bacteria such as Eschericia coli and Erwinia chrysanthemi.…”
Section: Extracellular Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from secreting lesser amount of enzymes, certain endophytes are extremely slow growing which further delays the enzyme secretion. Therefore, it is pivotal to boost their enzyme secretion employing modern techniques, like, cell factory engineering and CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR associated protein) technology ( Raghav et al, 2022 ). Neverthless, such modifications may hike the overall cost for synthesizing endophytic enzymes.…”
Section: Methods Of Lignin Depolymerizationmentioning
confidence: 99%
“…More than 700 commercial enzyme-based products are extensively used in an array of over 40 different industrial sectors, which include the detergent and textile industries, food processing, medical therapeutics, pharmaceuticals and also for agricultural purposes (Sopalun and Iamtham 2020;Raghav et al, 2022). There is a need to explore new sustainable sources for enzyme production with enriched biological applications, fungal endophytes have been demonstrated as good sources of enzymes of industrial interest (Raghav et al, 2022).…”
Section: Introductionmentioning
confidence: 99%